Analysis of the 90SR content in grassland vegetation when placed in leached chernozem - V. A. Pogorelova; B. S. Tsipinova; A. I. Melchenko (Новые технологии)
Nuclear power continues to develop rapidly in the 21st century. Due to the growth of the population on the planet and the growth of its well-being, more energy is required, which nuclear energy can also provide. Currently, work to improve the reactors used at nuclear power plants is going on. However, unfortunately, there are no guarantees for their trouble-free operation. Therefore, in case of possible accidents and radioactive contamination of the soil, the question arises of its further use in agricultural production. The return of radioactively contaminated fertile lands to agricultural production is the most important task at the present stage of human life. The purpose of the research is to study the content of specific activity in grassland vegetation, depending on its type, when the nuclide is located in the soil at a depth of 50 cm. The migration and accumulation of 90SR in grassland vegetation located in the orchard in the soil at a depth of 50 cm has been studied. The study of the accumulation of radionuclides in agricultural plants and soil after its radioactive contamination is one of the most urgent problems of our time. A field experiment has been carried out in a fruit seed orchard. Grassland vegetation is the most valuable bioresource, that is, it is a potential food for domestic and wild animals, so it is important to make a forecast of its possible use. Accumulation of the radionuclide in grassland vegetation along the trophic chain can lead to its accumulation in the human body. The largest accumulation of 90SR in annual herbaceous vegetation, as a possible fodder bioresource, when the radionuclide is located in the soil at a depth of 50 cm, is distinguished by field bindweed. In 2019, the difference in the accumulation of the nuclide between field bindweed and couch grass was 2.5 times. A decreasing series is compiled for the accumulation of the radionuclide, when it is located in the soil at a depth of 50 cm: field bindweed (Convolvulus arvensis L.) > field dandelion (Taraxacum officinale) = field sow thistle (Sonchus arvensis L.) > creeping couch grass (Agropyrum repens L.) > common yarrow (Achillea millefolium L.).